Workhsop Desain Surat Resmi Secara Profesional di SMK Negeri 1 Setia Janji - Andri Nata; Maulana Dwi Sena; Fauriatun Helmiah; Maulana Fikri (STMIK Royal, 2026)
Abstract: This workshop activity aims to improve students' understanding and skills in compiling and designing official letters in accordance with applicable writing rules. The workshop was held at SMK Negeri 1 Setia Janji with participants from various departments. The material presented includes the format of official letters, the language used, and good and correct layout. In its implementation, participants were guided directly using Microsoft Office Word software as the main tool in making official letters. The training method was carried out through material presentation, case studies, and direct practice. The evaluation results showed an increase in students' understanding of the structure of official letters and technical skills in designing letters using Microsoft Word features. This workshop is expected to be a practical provision for students in facing formal administrative needs both in the world of education and the world of work. In addition, this activity also encourages students to be more accustomed to using word processing applications professionally. Keywords: workshop; official letter; SMK; microsoft word. Abstrak: Kegiatan workshop ini bertujuan untuk meningkatkan pemahaman dan keterampilan siswa dalam menyusun serta mendesain surat resmi sesuai dengan kaidah penulisan yang berlaku. Workshop dilaksanakan di SMK Negeri 1 Setia Janji dengan melibatkan peserta dari berbagai jurusan. Materi yang disampaikan meliputi format surat resmi, penggunaan bahasa yang tepat, serta tata letak yang baik dan benar. Dalam pelaksanaannya, peserta dibimbing secara langsung menggunakan perangkat lunak Microsoft Office Word sebagai alat utama dalam pembuatan surat resmi. Metode pelatihan dilakukan melalui penyampaian materi, studi kasus, dan praktik langsung. Hasil evaluasi menunjukkan adanya peningkatan pemahaman siswa terhadap struktur surat resmi serta keterampilan teknis dalam mendesain surat menggunakan fitur-fitur Microsoft Word. Workshop ini diharapkan dapat menjadi bekal praktis bagi siswa dalam menghadapi kebutuhan administrasi formal baik di dunia pendidikan maupun dunia kerja. Selain itu, kegiatan ini juga mendorong siswa untuk lebih terbiasa menggunakan aplikasi pengolah kata secara profesional. Kata kunci: workshop; surat resmi; SMK; Microsoft Word.